Evaluasi User Interface Website Prodi Teknik Informatika UNRI Menggunakan User Experience Questionnaire (UEQ) - Edi Susilo; Rahmat Rizal Andhi; Dian Ramadhani (Fakultas Teknik Universitas Hamzanwadi, 2022)
The current website of Informatics Programme at Riau University is being redesign. This process need to be done because the past design had a few shortcomings, such as not being responsive and less attactive to user, in term of UI. To figure out weather the new design meets the UX aspects, it is necessary to make an evaluation. This research does that evaluation about current website User Interface (UI) using UEQ. UEQ,as for today, is consider a fast and simple tools to test UX aspects of certain website. The UEQ will be distributed to 50 respondents which is Informatics Programme’s student. This respondent consist of 25 men and 25 women. Respondent data was analyzed using UEQ Data Analysis Tools. The result was 4 aspects which is consider good, such as attractiveness, efficiency, dependability and stimulation. There was 1 aspect which score above average, namely perspicuity. One last aspect was score below average, which is novelty. From this research result, in general the UI design and UX aspects of this website is consider good. However, to reach maximum performance some adjustment need to be done. Especially from the perspicuity ascpect. The developer need to clarify the way to use this website. The approach can be taken from general web design principal. As for novelty aspects, improvement need to be done to its content with creative and inovatif idea. This will bring unique value for informatics programme website compare to another sites.